Strategic construal of in and out in English particle verbs (PVs) - Geld, Renata (Array, 2011)
The central aim of this work is to describe the strategic construal of in and out in English particle verbs. The term strategic construal assumes the following: 1) exploration of strategic thinking in L2 learning and processing, and 2) exploration of dynamic and subjective construction of meaning pertaining to the human ability to understand and portray the same situation in alternate ways (Langacker 1987). In other words, the paper relies on two theoretical paradigms with self-evident commonalities – a strong link between language and cognition, and the insistence on the individual and subjective nature of meaning construction. The aim was to investigate whether L2 users of English are aware of the symbolic nature of language when dealing with highly schematic linguistic categories. Our hypotheses were that construal of in and out is comparable to their cognitive linguistic description in English as L1 and that it shows a cognitively motivated path from the topological to the aspectual. Both hypotheses have been confirmed.